Opinions and clinical practices related to diagnosing and managing functional (psychogenic) movement disorders: changes in the last decade. (2nd April 2020) - LaFaver, K.; Lang, A. E.; Stone, J.; Morgante, F.; Edwards, M.; Lidstone, S.; Maurer, C. W.; Hallett, M.; Dwivedi, A. K.; Espay, A. J.
Abstract : Background and purpose: There is large variability in the diagnostic approach and clinical management in functional movement disorders (FMD). This study aimed to examine whether opinions and clinical practices related to FMD have changed over the past decade. Methods: Adapted from a 2008 version, we repeated the survey to members of the International Parkinson and Movement Disorder Society (MDS). Results: In all, 864/7689 responses (denominator includes non‐neurologists) were received from 92 countries. Respondents were more often male (55%), younger than 45 (65%) and from academic practices (85%). Although the likelihood of ordering neurological investigations prior to delivering a diagnosis of FMD was nearly as high as in 2008 (47% vs. 51%), the percentage of respondents communicating the diagnosis without requesting additional tests increased (27% vs. 19%; P  = 0.003), with most envisioning their role as providing a diagnosis and coordinating management (57% vs. 40%; P  < 0.001). Compared to patients with other disorders, 64% of respondents were more concerned about missing a diagnosis of another neurological disorder. Avoiding iatrogenic harm (58%) and educating patients about the diagnosis (53%) were again rated as the most effective therapeutic options. Frequent treatment barriers included lack of physician knowledge and training (32%), lack of treatment guidelines (39%), limited availability of referral services (48%) and cultural beliefs about psychological illnesses (50%). The preferred term for communication favored 'functional' over 'psychogenic' ( P  < 0.001). Conclusions: Attitudes and management of FMDs have changed over the past decade. Important gaps remain in access to treatment and in the education of neurologists about the inclusionary approach to FMD diagnosis.